Novel Genetic Loci Associated With Retinal Microvascular Diameter. (February 2016) - Jensen, Richard A.; Sim, Xueling; Smith, Albert Vernon; Li, Xiaohui; Jakobsdóttir, Jóhanna; Cheng, Ching-Yu; Brody, Jennifer A.; Cotch, Mary Frances; Mcknight, Barbara; Klein, Ronald; Wang, Jie Jin; Kifley, Annette; et al.
Abstract : Background—: There is increasing evidence that retinal microvascular diameters are associated with cardiovascular and cerebrovascular conditions. The shared genetic effects of these associations are currently unknown. The aim of this study was to increase our understanding of the genetic factors that mediate retinal vessel size. Methods and Results—: This study extends previous genome-wide association study results using 24 000+ multiethnic participants from 7 discovery cohorts and 5000+ subjects of European ancestry from 2 replication cohorts. Using the Illumina HumanExome BeadChip, we investigate the association of single-nucleotide polymorphisms and variants collectively across genes with summary measures of retinal vessel diameters, referred to as the central retinal venule equivalent and the central retinal arteriole equivalent. We report 4 new loci associated with central retinal venule equivalent, one of which is also associated with central retinal arteriole equivalent. The 4 single-nucleotide polymorphisms are rs7926971 in TEAD1 ( P =3.1×10 − 11 ; minor allele frequency=0.43), rs201259422 in TSPAN10 ( P =4.4×10 −9 ; minor allele frequency=0.27), rs5442 in GNB3 ( P =7.0×10 −10 ; minor allele frequency=0.05), and rs1800407 in OCA2 ( P =3.4×10 −8 ; minor allele frequency=0.05). The latter single-nucleotide polymorphism, rs1800407, was also associated with central retinal arteriole equivalent ( P =6.5×10 −12 ). Results from the gene-based burden tests were null. In phenotype look-ups, single-nucleotide polymorphism rs201255422 was associated with both systolic ( P =0.001) and diastolic blood pressures ( P =8.3×10 −04 ). Conclusions—: Our study expands the understanding of genetic factors influencing the size of the retinal microvasculature. These findings may also provide insight into the relationship between retinal and systemic microvascular disease. Abstract : Supplemental Digital Content is available in the text.